PENGARUH DARI KUALITAS KERJA DAN PENGAWASAN TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAN DIKLAT KABUPATEN MINAHASA SELATAN - Ulaan, Pingkan Elizabeth; Areros, William A.; Kalangi, Johnny F. (Sam Ratulangi University, 2022)
This study aims to determine whether there is an effect of work quality and monitoring on employee performance in the Personnel and Training Agency of South Minahasa Regency. This research uses quantitative research methods. In this study, there are two variables, namely the independent variable (X) and the dependent variable (Y) where the independent variable (independent) is the quality of work and supervision and the dependent variable (dependent) in this study is employee performance. The data analysis carried out in this study was instrument test, classical assumption test, and multiple linear regression analysis. The results of the study indicate that the quality of work, supervision, and both simultaneously affect the performance of employees at the Personnel and Training Agency of South Minahasa Regency. Through the determination test, it was found that the effect of work quality and supervision was 52.6%, the remaining 47.4% was explained by other variables not examined in this study.